2013
DOI: 10.1073/pnas.1218072110
|View full text |Cite
|
Sign up to set email alerts
|

Brg1 governs distinct pathways to direct multiple aspects of mammalian neural crest cell development

Abstract: Development of the cerebral vessels, pharyngeal arch arteries (PAAs). and cardiac outflow tract (OFT) requires multipotent neural crest cells (NCCs) that migrate from the neural tube to target tissue destinations. Little is known about how mammalian NCC development is orchestrated by gene programming at the chromatin level, however. Here we show that Brahma-related gene 1 (Brg1), an ATPase subunit of the Brg1/Brahma-associated factor (BAF) chromatin-remodeling complex, is required in NCCs to direct cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 47 publications
8
61
0
Order By: Relevance
“…In addition, inactivating mutations in Brg1 and other subunits of SWI/SNF complexes have been identified in various human cancers, including the pancreas and intestine (Helming et al, 2014;Wilson and Roberts, 2011). Furthermore, Brg1 is involved in cell proliferation during embryonic development (Hang et al, 2010;Seo et al, 2005;Li et al, 2013), a period in which Brg1 depletion increases the number of proliferative cells in neural plate (Seo et al, 2005). In line with these data, we found that the number of proliferative cells was elevated in Brg1-deficient duodenum.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In addition, inactivating mutations in Brg1 and other subunits of SWI/SNF complexes have been identified in various human cancers, including the pancreas and intestine (Helming et al, 2014;Wilson and Roberts, 2011). Furthermore, Brg1 is involved in cell proliferation during embryonic development (Hang et al, 2010;Seo et al, 2005;Li et al, 2013), a period in which Brg1 depletion increases the number of proliferative cells in neural plate (Seo et al, 2005). In line with these data, we found that the number of proliferative cells was elevated in Brg1-deficient duodenum.…”
Section: Discussionsupporting
confidence: 85%
“…Brg1 is required for inhibition of apoptosis in the development of various cell types and organs, including neurons (Li et al, 2013), smooth muscle (Zhang et al, 2011) and blood cells (Griffin et al, 2008); consequently, knockout of Brg1 increases the rate of apoptosis in these tissues. Our data showing that elevated apoptosis was reversed by Notch1 ICD overexpression in VBN mice demonstrate that marked downregulation of Notch signaling is responsible for increased apoptosis in Brg1-deficient duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that the histone H3K9me3/H3K36me3 demethylase JmjD2A regulates neural crest specification in the chick (StroblMazzulla et al, 2010), and the PRC1 component Ring1b specifically modulates craniofacial chondrocyte differentiation in zebrafish without affecting early induction and migration of the neural crest (van der Velden et al, 2013). Several components of chromatin remodeling complexes, such as Brg1 and CHD7, have also been reported to influence neural crest induction and/or differentiation (Eroglu et al, 2006;Bajpai et al, 2010;Weider et al, 2012;Li et al, 2013). Furthermore, both microRNA-processing enzymes and several specific microRNAs have been shown to regulate neural crest migration or affect neural crest-derived tissues, such as cranial and cardiovascular structures (Prasad et al, 2012;Strobl-Mazzulla et al, 2012;Mayanil, 2013).…”
Section: Discussionmentioning
confidence: 99%